Admission Process of Low Risk Women in Labour: Development of an Evidence-based Protocol - Abasian kasegari, Freshteh; Pazandeh, Farzaneh; Darvish narengbon, Sudabeh; Ghanbarpour, Azita (Advances in Nursing & Midwifery, 2019)
Abstract Introduction: To protect normal birth, admission of pregnant women in labour units is one of the most important decisions. This study developed a protocol for admission of women during labour in order to improve the accuracy of the diagnosis of onset of labour. Methods: First the admission processes of 25 pregnant women were observed in the study hospital. Then the multi-disciplinary team searched and reviewed the Iranian database using related key words. Evidence-based medicine resources and other databases were searched using related key words for the most important symptoms in relation to the onset of active labour as well as early labour assessment programs. Results: The results of observation of the admission process in the study hospital and review of the literature indicated that low-risk pregnant women in labour were admitted using different criteria. The evidence-based protocol for admission of women in labour was developed using these criteria to provide a guide, which lists the necessary measures in dealing with women in various situations during the onset of labour. Presence of regular uterine contractions, cervical dilatation ≥ 4 cm and effacement should be considered as signs of starting labour, which may be accompanied by spontaneous rupture of membranes or bloody show. Conclusions: Protocols are appropriate clinical tools for the design and standardization of clinical processes based on the available evidence. This protocol could be used in a multi-center clinical trial to assess its effectiveness.